The secrets of facilitation : the SMART guide to getting results with groups - Wilkinson, Michael, 1957- (San Francisco : Jossey-Bass, 2012)
'This thoroughly revised and updated edition of The Secrets of Facilitation delivers a clear vision of facilitation excellence and reveals the specific techniques effective facilitators use to produce consistent, repeatable results with groups. Author Michael Wilkinson has trained thousands of managers, analysts, and consultants around the world to apply the power of SMART (Structured Meeting And Relating Techniques) facilitation to achieve amazing results with teams and task forces. This new edition includes new chapters that highlight such timely topics as: facilitating virtual meetings; facilitating very large groups; facilitating conferences; and building an internal facilitator capability. The book also offers new cross-cultural examples, and an ancillary website with forms, checklists and a sample facilitator guide'--
Includes bibliographical references and index.
Keywords: Group facilitation -- Handbooks, manuals, etc; Business meetings -- Handbooks, manuals, etc